2021
DOI: 10.14336/ad.2020.1008
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Positively Contributes to Drosophila Intestinal Homeostasis and Delays Aging through Targeting Imd

Abstract: The intestine, a high-turnover tissue, plays a critical role in regulating aging and health in both vertebrates and invertebrates. Maintaining the epithelial barrier function of the intestine by preserving innate immune homeostasis significantly delays aging and prevents mortality. In an effort to explore effective chemicals and materials that can improve intestinal integrity, we performed a nonbiased screen utilizing Drosophila as an animal model. We showed that long-term uptake of aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have shown that preventing the IMD signaling pathway in gut tissues positively contributes to the life longevity of Drosophila ( 15 , 41 43 ). We thus sought to identify whether dTrbd modulates lifespan via multiple domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that preventing the IMD signaling pathway in gut tissues positively contributes to the life longevity of Drosophila ( 15 , 41 43 ). We thus sought to identify whether dTrbd modulates lifespan via multiple domains.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mRNA levels of these AMP genes were relatively comparable between samples from c564 ts >GFP-dTrbd DNZF , c564 ts >GFP-dTrbd DLR , and the control flies (Figures 5A, B), suggesting both the NZF domain and the LR are required for dTrbd to negatively govern IMD signaling post microbial infection. Previous studies have shown that preventing the IMD signaling pathway in gut tissues positively contributes to the life longevity of Drosophila (15,(41)(42)(43). We thus sought to identify whether dTrbd modulates lifespan via multiple domains.…”
Section: Dtrbd Functions In Vivo Via Multiple Domainsmentioning
confidence: 99%
“…Western blot assays were performed as described previously ( 51 ). In brief, fat bodies were lysed in lysis buffer (150mM NaCl, 50mM Tris-HCl, pH=7.4, 10% glycerol, 0.5% TritonX-100, and 1mM PMSF).…”
Section: Methodsmentioning
confidence: 99%
“…One of the proposed antiaging mechanisms of aspirin is through its effect on the reduction of germline stem cells [ 262 ]. Another proposed mechanism is improving intestinal barrier function by restricting the K63-linked ubiquitination and preventing intestinal immune deficiency [ 264 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%